From theory to simulation to teach care for burn victims: case report. - de Souza Oliveira-Kumakura, Ana Railka; Silva, Juliany Lino Gomes; Gonçalves, Natália (Anna Nery School Journal of Nursing / Escola Anna Nery Revista de Enfermagem, 2018)
Aim: To report the experience of applying different teaching strategies on undergraduate nursing students caring for burn victims. Method: Experience report on the topic, "Nursing care for the patient with burns", for undergraduate nursing student education. Results: Teaching strategies during this course involved theoretical lecture, discussion of clinical cases, use of a virtual environment, and practice in a simulated environment. The students reported satisfaction with the tools used. Conclusion : It is important to incorporate different active teaching strategies, such as clinical simulation practices, e-learning, classes incorporating dialogue, case studies, and others, for undergraduate nursing education on caring for the burn victim.